The Religious Dimension of Mencius’ Theory of the Goodness of Human Nature: A Critique of Gaozi’s View - Tianyang Cai; Yun Chen (Religions)
This paper argues that the Confucian notion of the “goodness of human nature” (Xing Shan 性善) does not exclude a religious dimension by examining Mencius’ explanation of this theory. In his response to Gongduzi (公都子), Mencius articulates his understanding of the goodness of human nature. Combining this response with Mencius’ criticism of Gaozi, the two discussions can illuminate each other. Mencius opposes Gaozi’s approach that relies on facts (Qing 情) and talents (Cai才) to define human nature. He argues that such an approach stems from an inductive mode of cognition and a detached observer’s stance toward the world, leading to a perspective devoid of a spiritual world. In contrast, Mencius posits that individuals, beyond sensory perception, can use the faculty bestowed by Heaven to perceive a world infused with noble spirit (Hao Ran Zhi Qi 浩然之氣). The heart-mind, deriving from a transcendent Heaven (天), holds religious significance for Mencius and represents an entity we must serve. However, this does not mean abandoning moral life. On the contrary, Mencius asserts that serving Heaven involves facing moral situations directly, discerning righteousness, and anchoring the direction of one’s actions. In realizing oneself, one also contributes to the realization of others, a significant interpretation of “human nature” as Mencius conceives it. By integrating religious belief with secular life, Mencius grounds the latter in the former, imbuing Confucian thought on the goodness of human nature with an implicit reverence. This approach invites us to understand human life within the comprehensive connection with the universe.